Design of a water curtain to reduce accumulations of float coal dust in longwall returns - Seaman, Clara E. (Int J Min Sci Technol, 2020)
Accumulation of float coal dust (FCD) in underground mines is an explosion hazard that affects all underground coal mine workers. While this hazard is addressed by the application of rock dust, inadequate rock dusting practices can leave miners exposed to an explosion risk. Researchers at the National Institute for Occupational Safety and Health (NIOSH) have focused on developing a water curtain that removes FCD from the airstream, thereby reducing the buildup of FCD in mine airways. In this study, the number and spacing of the active sprays in the water curtain were varied to determine the optimal configuration to obtain peak knockdown efficiency (KE) while minimizing water consumption.